Microsphaeropsis arundinis skin and soft tissue infection in renal transplant recipients: three case reports and a review of the literature. Issue 6 (25th November 2015) - Crawford, S.J.; Chen, S.C.‐A.; Halliday, C.; Rangan, G.K.; Gottlieb, T.; Reid, A.B.
Abstract: Microsphaeropsis arundinis, a dematiaceous mold, is emerging as a cause of skin and soft tissue infection in immunocompromised hosts. Diagnosis is challenging because of the difficulty in identifying Microsphaeropsis species morphologically and few data are available to guide optimal management. We report 3 renal transplant recipients with M. arundinis soft tissue infection, where the etiological agent was diagnosed using DNA sequencing, and who were successfully treated with prolonged courses of extended‐spectrum triazole antifungal agents.